Evaluation of the AST/ALT Ratio as a Non-Invasive Predictor of Chronic Liver Disease - Nurul Ainun Annisa; Irna Diyana Kartika Kamaluddin; Muhammad Alim Jaya; Hasan Hasan; Ardiyanto Ardiyanto (Journal La Medihealtico, 2026)
This study evaluated the AST/ALT ratio as a non invasive predictor of liver fibrosis by examining its clinical utility, diagnostic relevance, and limitations in contemporary practice. Liver fibrosis is a progressive outcome of chronic liver injury that may develop into cirrhosis, liver failure, and hepatocellular carcinoma if not detected and managed early. Therefore, accessible non invasive markers are needed, particularly in settings with limited diagnostic resources. This study used an analytical literature review approach. Articles published within the last ten years were searched through PubMed, Google Scholar, and ScienceDirect using keywords related to AST/ALT, non invasive liver disease, liver fibrosis, and diagnosis. Relevant studies were selected based on predetermined inclusion and exclusion criteria, then analyzed descriptively and comparatively. The findings indicate that the AST/ALT ratio has potential as a simple, affordable, and widely available marker for the initial assessment of liver fibrosis. It showed a meaningful association with fibrosis severity, especially in patients with chronic hepatitis B and other chronic liver diseases. However, its diagnostic performance varied depending on disease etiology, fibrosis stage, and patient characteristics. Compared with APRI, FIB 4, FibroScan, and elastography, the AST/ALT ratio generally demonstrated only moderate accuracy and was less reliable as a standalone marker. Therefore, it is more appropriate as an initial screening tool or complementary indicator rather than a definitive diagnostic method.